Islamic Banks vs. Conventional Banks in Bangladesh: A Comparative Study Based on its Efficiency in Operation - Ahmad, Faisal (International Journal of Islamic Banking and Finance Research, 2020)
The main purpose of this study is to make a comparison between Islamic banks (IBs) and Conventional banks (CBs) in Bangladesh based on its efficiency in operation. The Data Envelopment Analysis (DEA) is employed under CRS and VRS approach, which allows for the decomposition of efficiency into technical, allocated and cost efficiency. The study also measures changes in productivity over the time as a result of technical progress by employing the Malmquist Total Factor Productivity Index. The results explain that the technical efficiency of IBs is better than that of CBs, but allocated and cost efficiency (CE) of IBs are higher than CBs. In Bangladesh there are 62 commercial banks included 8 Islamic Banks that are regulated by Bangladesh Bank (BB).